Teaching a second language to learners with mild intellectual disabilities – a Hungarian case study - Nemes, Magdolna (Frontiers in Education, 2024)
The present paper deals with the issues of teaching a second language to school-aged children in Hungary with mild intellectual disabilities. The frameworks for language teaching are described in the National Core Curriculum and the Frame Curriculum. In our research we conducted semi-structured interviews with open-ended questions featuring 11 language teachers, and asked for their experience in teaching a second language to children with mild intellectual disabilities. Moreover, our research involves a focus group discussion in spring 2023 featuring 8 children in Grade 7 with mild intellectual disabilities. We came to the conclusion that teachers pay attention to individual development and playful, communicative language teaching, even though it is challenging to teach English to children with such disabilities, as they often have difficulties in their mother tongue. The research has revealed there is a need for teachers to display creativity because these children require a lot of revision. The children asked do not encounter English at home and only a few of them listen to music in English. However, they all think learning English is important for their future, especially in the areas of work and travel. Our experience underlines that it is beneficial for learners with mild intellectual disabilities to get to know a foreign language, even though they will not be independent users of the language and might not use this knowledge in the future.